Impact of hidradenitis suppurativa on work loss, indirect costs and income. (22nd October 2018) - Tzellos, T.; Yang, H.; Mu, F.; Calimlim, B.; Signorovitch, J.
Summary: Background: Hidradenitis suppurativa (HS), a chronic cutaneous disease, can negatively affect work life. Objectives: This retrospective cohort study evaluates the indirect burden among employed patients with HS in the U.S.A. Methods: Newly diagnosed and general patients with HS, who were employees (age 18–64 years) from a large claims database (Q1 1999 to Q1 2015), were matched 1 : 5 to controls. Income growth and risk of leaving the workforce were assessed among the newly diagnosed HS and control cohorts in the 5‐year study period. Income, work loss days and indirect costs (absenteeism and disability) were assessed among the general HS and control cohorts in the 1‐year study period. Results: Newly diagnosed ( n = 1003, mean age 39·5 years, 66·3% female) and general patients with HS ( n = 1204, mean age 39·9 years, 69·1% female) were matched to 5015 and 6020 controls, respectively. Newly diagnosed patients with HS had significantly slower income growth (324 per year) and higher risk of leaving the workforce (adjusted hazard ratio 1·65, 95% confidence interval 1·45–1·88) compared with controls (all P < 0·05). General patients with HS had more total days of work loss (18·4 vs. 7·7), higher annual total indirect costs (2925 vs. 1483) and lower annual income (54 925 vs. 62 357) than controls (all P < 0·001). Conclusions: Patients with newly diagnosed HS and general patients with HS experienced a greater indirect burden than matched controls. Abstract : What's already known about this topic? Hidradenitis suppurativa (HS), a chronic inflammatory disease, can negatively affect work life. What does this study add? This retrospective claims analysis found that HS is associated with high indirect burden, in terms of slower income growth, higher risk of leaving the workforce and higher indirect costs. These results indicate that patients with HS have unmet disease management needs. Linked Editorial: Zouboulis. Br J Dermatol 2019; 181 :7–8 . Plain language summary available online Respond to this article